Transformation of Melodrama in Turkish Cinema from Yeşilçam to the Present: The Films Innocence and Destiny - Kemal Çelik (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2024)
Melodramas are dramatic works of art where the detailed character studies dominate the plot. The dialogues used in melodramas are generally emotional, and the characters are often portrayed in stereotypical forms. Melodramas usually focus on emotions like love. As a subgenre of drama films, melodramas carry the mentioned characteristics of this genre; thus, they have plotlines driven by powerful emotions such as love. Content-wise, melodrama films often deal with tragedies like hopeless love stories. Characters must struggle against significant social pressures from their lovers or families. Sacrifice is a fundamental tool for characters in this struggle. Yeşilçam melodramas adhere to the requirements of this genre. They typically revolve around an exalted love that could be noble and spiritual. Characters must fight for this love like medieval knights. The characters in these films are usually unfortunate, and their mistakes turn their lives into hell. Zeki Demirkubuz, an important director of the New Turkish Cinema, continues the tradition of melodrama as an inheritor of its themes. However, he differentiates himself from them in terms of how he approaches the concept of good and evil. This study examines the difference between these two understandings of melodrama through Demirkubuz's films "Innocence" and "Destiny" using content analysis and critical discourse analysis methods. Demirkubuz’s two films selected as samples carry the general characteristics of Yeşilçam melodramas such as exaggerated emotions, missed happiness, extremes, bipolar lives, event structures based on cause-and-effect relationships, monologue uses, music uses, while they differ from them at an important point. While Yeşilçam melodramas view humans as ontologically good beings despite their mistakes, Demirkubuz's cinema accepts humans as ontologically evil beings. This study will reveal that, unlike the previous studies’ theses, Demirkubuz’s cinema places evil at the center of its films through their event structures, dialogues and word choices, and thus turns upside down the approach of Yeşilçam melodramas to evil.